High-performance phenolic resin material and application thereof in precoated sand

By modifying the combination of phenolic resin and a variety of additives, a molecular network structure with high cross-linking density is formed, which solves the problems of high temperature resistance, toughness and anti-aging performance of coated sand coating materials under high temperature and high pressure conditions, and achieves high-efficiency curing and long-life material performance.

CN119823526APending Publication Date: 2025-04-15XINMI WANLI IND DEV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510037012.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing coating sand coating materials have insufficient high temperature resistance under high temperature conditions, difficult to take into account both toughness and strength, low curing efficiency and poor anti-aging performance under high temperature and high pressure conditions.

Method used

Modified phenolic resin is used as the main matrix material, and the modification is made by introducing functional groups (such as hydroxyl, epoxy or carboxyl groups) to form a molecular network structure with high cross-linking density, and metal salt-based curing accelerators, toughening agents, fillers and multifunctional additives are added to improve the material's heat resistance, curing rate, toughness and anti-aging properties.

Benefits of technology

It achieves the maintenance of high mechanical strength and stability under high temperature conditions, significantly shortens the curing time, improves the toughness and impact resistance of the material, and extends the service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119823526A_ABST
    Figure CN119823526A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of petrochemical proppants, and discloses a high-performance phenolic resin material which comprises the following components in percentage by weight: 60%-75% of modified phenolic resin, 5%-15% of a curing accelerator, 10%-20% of a flexibilizer, 5%-20% of a filler and 3%-10% of a multifunctional additive, the modified phenolic resin is prepared by the following steps: mixing a phenolic compound and a formaldehyde solution in a reaction kettle, adding a basic catalyst, and reacting to obtain a phenolic prepolymer; gradually adding a modifier containing a hydroxyl group, an epoxy group and a carboxyl group into the phenolic prepolymer, and simultaneously stirring to obtain a mixture; heating the obtained mixture for reaction to complete crosslinking modification reaction to obtain modified phenolic resin; and cooling the modified phenolic resin to room temperature for later use. By adopting the design of the multifunctional flexibilizer and the composite filler, the toughness and thermal conductivity of the material are improved, meanwhile, the curing efficiency is accelerated through the curing accelerator, and the industrial cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of petrochemical proppants, in particular to a high-performance phenolic resin material and application thereof to coated sand. Background Art

[0002] The oil fracturing process is a key technology to improve the efficiency of oil and gas field extraction. Among them, coated sand plays an important role as a proppant material in the fracturing operation of oil wells. Coated sand is coated with resin material on the surface of quartz sand to enhance its mechanical strength and chemical corrosion resistance, so as to meet the use requirements under high temperature and high pressure environment. At present, the coating material of traditional coated sand is mainly unmodified phenolic resin or thermoplastic resin.

[0003] Phenolic resin has become an important choice in coated sand applications due to its excellent high temperature resistance and high strength after curing. However, under existing technical conditions, unmodified phenolic resin generally has the following technical defects: in a high temperature environment exceeding 150°C, the molecular network structure of traditional phenolic resin undergoes thermal softening or degradation, resulting in a significant decrease in the compressive strength of the coated sand. The curing process of unmodified phenolic resin relies on heat-induced cross-linking, which requires a higher curing temperature and a longer curing time, making it difficult to meet the needs of rapid construction. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present invention provides a high-performance phenolic resin material and its application in coated sand, which solves the problems of insufficient high-temperature resistance, difficulty in balancing toughness and strength, low curing efficiency and poor anti-aging performance of existing coated sand coating materials under high temperature and high pressure conditions.

[0005] To achieve the above objectives, the present invention is implemented by the following technical scheme: a high-performance phenolic resin material, the material comprises the following components by weight percentage: Modified phenolic resin 60% to 75%, the modified phenolic resin is the main matrix material of the present invention, and its high crosslinking density gives the material excellent high temperature resistance and mechanical strength. The molecular structure is adjusted through the modification process, so that functional groups (such as hydroxyl, epoxy or carboxyl) are introduced into the molecular chain, which improves the heat resistance and chemical stability of the phenolic resin, and at the same time enhances the interface bonding performance with other components (such as fillers, toughening agents).

[0006] Curing accelerator 5% to 15%, metal salt curing accelerator can significantly increase the curing reaction rate and shorten the curing time, thus meeting the needs of rapid industrial production. Through the catalytic effect of metal ions, the activation energy between phenolic resin and curing agent is reduced, and the cross-linking formation between resin molecules is promoted.

[0007] The toughening agent is 10% to 20%. The introduction of the toughening agent improves the defect of brittleness of phenolic resin after curing. It forms a flexible phase by dispersing in the phenolic resin matrix and absorbs impact energy, thereby significantly improving the toughness and impact performance of the material. The combination of low molecular weight polyether and liquid crystal polymer can further optimize the processability of the system.

[0008] Filling material 5% to 20%; The addition of fillers not only plays a role in volume compensation, but also improves the mechanical properties and high temperature resistance of the material through the interface enhancement effect. For example, the thermal conductivity of boron nitride and graphene significantly improves the heat dissipation efficiency of the material, while zirconium oxide ceramic powder enhances the wear resistance and chemical corrosion resistance of the material.

[0009] Multifunctional additive 3% to 10%.

[0010] The introduction of multifunctional additives such as UV stabilizers and antioxidants can delay the aging process of materials in harsh environments and increase their service life; rust inhibitors further enhance the corrosion resistance of the materials, especially in the high-salinity environment of oil and gas extraction.

[0011] Preferably, the modified phenolic resin is prepared by the following steps: The phenolic compound and the formaldehyde solution are mixed in a reaction kettle, and an alkaline catalyst is added to react to obtain a phenolic prepolymer; the polycondensation reaction of the phenolic compound and formaldehyde is the basis for the preparation of phenolic resins. The hydroxymethylation reaction of the phenolic hydroxyl group and the formaldehyde is promoted by the action of an alkaline catalyst (such as sodium hydroxide or calcium hydroxide) to generate a phenolic prepolymer with reactive activity.

[0012] gradually adding a modifier containing a hydroxyl group, an epoxy group, and a carboxyl group to the phenolic prepolymer while stirring to obtain a mixture; The introduction of the modifier has a functional enhancement effect on the structure of the phenolic resin molecular chain. The hydroxyl and carboxyl groups can form a stable bond with the matrix material through hydrogen bonds, while the epoxy groups can further cross-link with the resin molecules during subsequent curing, thereby improving the heat resistance and mechanical strength of the phenolic resin.

[0013] The obtained mixture is heated to react to complete the cross-linking modification reaction to obtain a modified phenolic resin; The heating reaction further promotes the chemical combination between the prepolymer and the modifier, and triggers the cross-linking reaction of the phenolic resin to form a network structure with a high cross-linking density. This structure provides the phenolic resin with excellent high temperature resistance, chemical stability and mechanical strength.

[0014] The modified phenolic resin is cooled to room temperature and then used for later use.

[0015] The cooling process is crucial to the material properties. Slow cooling can avoid the accumulation of internal thermal stress, while stabilizing the cross-linked structure and ensuring the uniformity of material properties.

[0016] Preferably, the curing accelerator is one or more metal salt compounds, and the metal salt compounds include cobalt acetate and zinc acetate.

[0017] Metal salt catalysts coordinate with hydroxymethyl or active groups to reduce the activation energy of the reaction, significantly accelerate the curing process, and improve production efficiency.

[0018] Preferably, the toughening agent is one or more of low molecular weight polyether, liquid crystal polymer or polyurethane prepolymer.

[0019] The combination of polyether and liquid crystal polymer forms a flexible dispersed phase in the matrix, which effectively slows down the crack propagation of the material under impact load.

[0020] Preferably, the filler includes one or more of the following: Boron nitride, graphene, carbon nanotubes, zirconium oxide ceramic powder, surface modified glass microspheres.

[0021] Preferably, the multifunctional additive comprises one or more of the following: UV stabilizer, antioxidant, rust inhibitor.

[0022] A method for preparing a high-performance phenolic resin material comprises the following steps: S1. In a reaction kettle, dissolving the modified phenolic resin in an organic solvent to form a uniform solution; S2, gradually adding a curing accelerator, a toughening agent and a filler to the solution, stirring and mixing until uniformly dispersed; S3, preliminarily curing the mixed solution to form a cured prepolymer; S4, further heating the cured prepolymer for secondary curing to obtain a high-performance phenolic resin material; S5. Cool the solidified product to room temperature and crush it into granules.

[0023] Preferably, the dissolution process of the modified phenolic resin in step S1 is carried out at a temperature of 60 to 80° C., and the filler in step S2 is uniformly dispersed by ultrasonic vibration or high shear stirring equipment, with a stirring rate of 5000 to 6000 rpm and a dispersion time of 10 to 30 minutes.

[0024] The preliminary curing in step S3 is carried out by controlling the temperature at 100-120° C. for 1-2 hours, and the curing degree reaches 70%-80%; The secondary curing in step S4 is carried out at a temperature of 150 to 180° C. for 1 to 2 hours, and further cross-linked to complete curing; The solidified product after cooling in step S5 is crushed by a mechanical crusher to prepare a granular high-performance phenolic resin material with a particle size of 10 to 50 microns.

[0025] The invention discloses a coated sand, wherein the coating material of the coated sand adopts a high-performance phenolic resin material.

[0026] The present invention provides a high-performance phenolic resin material and its application in coated sand, which has the following beneficial effects: 1. The present invention adopts modified phenolic resin as the main matrix material, and forms a molecular network structure with high cross-linking density by introducing a compound containing hydroxyl, epoxy or carboxyl into the phenolic prepolymer for modification, thereby achieving the technical effect of maintaining high mechanical strength and stability under high temperature conditions. Compared with the technical solution of using unmodified phenolic resin as the matrix material in the prior art, the problems of decreased mechanical properties, easy softening and insufficient heat resistance under high temperature environment are solved.

[0027] 2. The present invention uses metal salt compounds as curing accelerators, such as cobalt acetate and zinc acetate, to reduce the activation energy of the curing reaction of the phenolic resin and accelerate the curing reaction rate, thereby achieving the technical effect of significantly shortening the curing time and adapting to the needs of rapid industrial production. Compared with the technical solution of the prior art in which the curing time of ordinary catalysts is long, the shortcomings of low production efficiency and difficulty in meeting large-scale application requirements are solved.

[0028] 3. The present invention uses low molecular weight polyether, liquid crystal polymer or polyurethane prepolymer as a toughening agent to form a flexible dispersed phase in the matrix, improves the toughness of the material by absorbing impact energy, and achieves the technical effect of significantly improving the impact resistance of the material and reducing brittleness. Compared with the technical solution in the prior art that does not add a toughening agent or has an insignificant toughening effect, it solves the problem of high brittleness of the material and easy cracking or damage.

[0029] 4. The present invention delays the aging process of the material in a harsh environment by adding multifunctional additives, including UV stabilizers, antioxidants and rust inhibitors, to the formula, thereby achieving the technical effect of improving the corrosion resistance and anti-aging performance of the material and extending the service life. Compared with the technical solution in the prior art that the material is prone to corrosion and aging under high salinity and strong ultraviolet conditions, the shortcomings of poor adaptability and short service life are solved. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 It is a flow chart of the preparation method of the present invention. DETAILED DESCRIPTION

[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] Please refer to the attached Figure 1 : Example: Embodiment 1: Material formula Modified phenolic resin: 70% Curing accelerator (cobalt acetate): 10% Toughening agent (low molecular weight polyether, molecular weight 2000): 10% Filler (zirconia ceramic powder): 5% Multifunctional additive (antioxidant + UV stabilizer, 1:1): 5%.

[0033] Preparation steps Preparation of phenolic prepolymer: Phenol and 37% formaldehyde solution were mixed in a reaction kettle at a molar ratio of 1:1.2, and sodium hydroxide (mass fraction 0.8%) was added as a catalyst.

[0034] The reaction temperature was controlled at 70° C. and the reaction was carried out for 2 hours to obtain a viscous phenolic prepolymer.

[0035] Preparation of modified phenolic resin: Glycidol was gradually added to the phenolic prepolymer at a stirring rate of 400 rpm and stirring was continued for 2 hours to complete the initial modification.

[0036] The mixture was heated to 90° C. and the reaction was maintained for 3 hours to obtain a modified phenolic resin with a high cross-linking density.

[0037] Material compounding: The modified phenolic resin was dissolved in an ethanol solvent in a reaction kettle at a dissolving temperature of 70°C.

[0038] Cobalt acetate, low molecular weight polyether, zirconium oxide ceramic powder and antioxidant + ultraviolet stabilizer were added to the solution in sequence, and the solution was stirred for 30 minutes at a stirring rate of 6000 rpm using a high shear stirring device.

[0039] Curing and post-processing: The initial curing temperature is 120°C for 1.5 hours, followed by a secondary curing temperature of 160°C for 2 hours to form a fully cured high-performance phenolic resin.

[0040] After cooling to room temperature, the solidified product was crushed into particles with a particle size of 30 μm using a mechanical crusher.

[0041] This embodiment demonstrates the high temperature resistance and high strength of the modified phenolic resin. The curing rate is significantly accelerated by using cobalt acetate as a curing accelerator. Meanwhile, the introduction of low molecular weight polyether effectively improves the brittleness of the matrix.

[0042] Embodiment 2: Material formula Modified phenolic resin: 65% Curing accelerator (zinc acetate): 8% Toughening agent (liquid crystal polymer + polyurethane prepolymer, 1:1): 15% Filler (carbon nanotubes + zirconium oxide ceramic powder, 1:1): 7% Multifunctional additive (UV stabilizer): 5%.

[0043] Preparation steps Preparation of phenolic prepolymer: The same process as in Example 1 was used to prepare the phenolic prepolymer.

[0044] Preparation of modified phenolic resin: Glycidol and trimethylolamine were added to the phenolic prepolymer at a stirring rate of 500 rpm for 1.5 hours.

[0045] The mixture was heated to 95° C. and the reaction was maintained for 3 hours to obtain a modified phenolic resin.

[0046] Material compounding: The modified phenolic resin was dissolved in a mixed solvent (toluene and ethanol, 1:1) in a reaction kettle at a dissolution temperature of 70°C.

[0047] Zinc acetate, liquid crystal polymer, polyurethane prepolymer, carbon nanotubes, zirconium oxide ceramic powder and ultraviolet stabilizer were added in sequence and dispersed by ultrasonic vibration equipment for 20 minutes.

[0048] Curing and post-processing: The primary curing temperature is 110°C for 1.5 hours, and the secondary curing temperature is 170°C for 2 hours to obtain a fully cured material.

[0049] After cooling, the mixture was crushed into particles with a particle size of 25 microns.

[0050] Summary of Examples By introducing a toughening agent of a combination of liquid crystal polymer and polyurethane prepolymer, this embodiment further improves the toughness of the material. Compared with the basic embodiment, although the tensile strength is slightly improved, the more significant improvement is reflected in the impact resistance. The efficiency of zinc acetate as a curing accelerator is slightly lower than that of cobalt acetate, and the curing rate is slightly slower, but the overall toughness is higher.

[0051] Embodiment 3: Material formula Modified phenolic resin: 60% Curing accelerator (cobalt acetate + zinc acetate, 1:1): 10% Toughening agent (polyether): 10% Filler (boron nitride + graphene, 1:1): 15% Multifunctional additive (rust inhibitor): 5% Preparation steps Preparation of phenolic prepolymer: same as Example 1.

[0052] Preparation of modified phenolic resin: A carboxyl-containing modifier (such as citric acid) was added to the phenolic prepolymer at a stirring rate of 300 rpm for 2 hours.

[0053] The mixture was heated to 85°C and reacted for 2 hours to obtain a modified phenolic resin.

[0054] Material compounding: The modified phenolic resin is dissolved in ethanol solvent at a dissolution temperature of 60°C.

[0055] Cobalt acetate, zinc acetate, polyether, boron nitride and graphene were added in sequence, and a high shear stirring device was used with a stirring rate of 5000 rpm and a dispersion time of 25 minutes.

[0056] Curing and post-processing: The initial curing temperature is 110°C for 2 hours, and the secondary curing temperature is 180°C for 1.5 hours. After cooling, the mixture is crushed into particles with a particle size of 20 microns.

[0057] Summary of Examples By using boron nitride and graphene fillers, this embodiment significantly improves the thermal conductivity of the material and is suitable for applications in high-heat environments. Compared with Example 1, although the material toughness is slightly lower, a significant breakthrough in high thermal conductivity is achieved.

[0058] Comparative Example: Comparative Example 1: Preparation process of comparative example 1 Material formula Modified phenolic resin: 70% Curing accelerator (cobalt acetate): None Toughening agent (low molecular weight polyether, molecular weight 2000): 10% Filler (zirconia ceramic powder): 5% Multifunctional additive (antioxidant + UV stabilizer, 1:1): 5% Preparation steps The preparation of phenolic prepolymer is the same as in Example 1.

[0059] The preparation of the modified phenolic resin is the same as that in Example 1.

[0060] Material compounding: The modified phenolic resin is dissolved in an ethanol solvent in a reaction kettle at a dissolving temperature of 70°C; Low molecular weight polyether, zirconium oxide ceramic powder and antioxidant + ultraviolet stabilizer were added to the solution in sequence, and the solution was stirred for 30 minutes at a stirring rate of 6000 rpm using a high shear stirring device.

[0061] Curing and post-processing: The initial curing temperature is 120°C and the time is 1.5 hours; The secondary curing temperature is 160°C and the time is 2 hours; After cooling to room temperature, the mixture was crushed into particles of 30 microns.

[0062] In this comparative experiment, the curing accelerator cobalt acetate was eliminated, and the curing reaction completely relied on the natural curing process of the phenolic resin, which was used to verify the necessity of the curing accelerator in shortening the curing time and improving the degree of cross-linking.

[0063] Comparative Example 2: Preparation process of comparative example 2 Material formula Modified phenolic resin: 65% Curing accelerator (zinc acetate): 8% Toughener (single liquid crystal polymer): 15% Filler (carbon nanotubes + zirconium oxide ceramic powder, 1:1): 7% Multifunctional additive (UV stabilizer): 5% Preparation steps The preparation of phenolic prepolymer is the same as in Example 2.

[0064] The preparation of the modified phenolic resin is the same as that in Example 2.

[0065] Material compounding: The modified phenolic resin was dissolved in a mixed solvent (toluene and ethanol, 1:1) at a dissolution temperature of 70°C; Zinc acetate, single liquid crystal polymer, carbon nanotubes, zirconium oxide ceramic powder and ultraviolet stabilizer were added in sequence and dispersed by ultrasonic vibration equipment for 20 minutes.

[0066] Curing and post-processing: The initial curing temperature is 110°C and the time is 1.5 hours; The secondary curing temperature is 170°C and the time is 2 hours; After cooling, the mixture was crushed to 25 micron particles.

[0067] In this comparative experiment, the toughening agent of Example 2 was changed from a combination of "liquid crystal polymer + polyurethane prepolymer" to a single liquid crystal polymer, in order to verify whether the synergistic effect of the two-component toughening agent is significant, and the effect on improving the toughness of the material.

[0068] Comparative Example 3: Preparation process of comparative example 3 Material formula Modified phenolic resin: 60% Curing accelerator (cobalt acetate + zinc acetate, 1:1): 10% Toughening agent (polyether): 10% Filler (single boron nitride): 15% Multifunctional additive (rust inhibitor): 5% Preparation steps The preparation of phenolic prepolymer is the same as in Example 3.

[0069] The preparation of the modified phenolic resin is the same as that in Example 3.

[0070] Material compounding: Dissolve the modified phenolic resin in ethanol solvent at a dissolving temperature of 60°C; Cobalt acetate, zinc acetate, polyether, boron nitride and rust inhibitor were added in sequence, and a high shear stirring device was used with a stirring rate of 5000 rpm and a dispersion time of 25 minutes.

[0071] Curing and post-processing: The initial curing temperature is 110°C and the time is 2 hours; The secondary curing temperature is 180°C and the time is 1.5 hours; After cooling, the mixture is crushed to 20 micron particles.

[0072] The filler in Example 3 was changed from "boron nitride + graphene" to single boron nitride to verify whether the composite thermally conductive filler has a significant improvement in thermal conductivity and the performance limitations of a single filler.

[0073] Comparative Example 4: Preparation process of comparative example 4 Material formula Modified phenolic resin: 70% Curing accelerator (cobalt acetate): 10% Toughening agent (low molecular weight polyether, molecular weight 2000): 10% Filler (zirconia ceramic powder): 5% Multifunctional additives: None Preparation steps The preparation of phenolic prepolymer is the same as in Example 1.

[0074] The preparation of the modified phenolic resin is the same as that in Example 1.

[0075] Material compounding: The modified phenolic resin is dissolved in ethanol solvent at a dissolution temperature of 70°C; Cobalt acetate, low molecular weight polyether and zirconium oxide ceramic powder were added in sequence, and stirred for 30 minutes at a stirring rate of 6000 rpm using a high shear stirring device.

[0076] Curing and post-processing: The initial curing temperature is 120°C and the time is 1.5 hours; The secondary curing temperature is 160°C and the time is 2 hours; After cooling to room temperature, the mixture was crushed into particles of 30 microns.

[0077] In this comparative example, multifunctional additives (such as antioxidants, UV stabilizers, rust inhibitors, etc.) were eliminated in order to verify the contribution of multifunctional additives to anti-aging performance, with a focus on examining the differences in performance degradation of materials under high temperature, UV irradiation and corrosive environments.

[0078] Experimental example: Experimental Example 1: Experimental procedures Sample preparation: Samples were prepared according to the formulas of Example 1 and Comparative Example 1: In Example 1, 10% of a curing accelerator (cobalt acetate) was added.

[0079] In Comparative Example 1, no curing accelerator was added.

[0080] The preparation and modification of the phenolic prepolymer were completed according to the steps of Example 1 and Comparative Example 1.

[0081] After the materials were compounded, the two groups of samples were placed in aluminum foil cups respectively.

[0082] Curing reaction test: Cure testing using Differential Scanning Calorimetry (DSC)**: The two groups of samples were placed in the DSC test cell respectively.

[0083] The heating rate was set to 10°C / min from room temperature to 200°C.

[0084] During the test, the heat flow signal of the sample is recorded, and the exothermic peak position and area of ​​the curing reaction are analyzed.

[0085] Data Records: The initial curing time is calculated from the onset temperature of the heat flow curve (the temperature point at which heat release begins).

[0086] The complete curing time is calculated by the termination temperature of the heat flow curve (the temperature point at which the exotherm ends).

[0087] The extent of the curing reaction was estimated by the exothermic peak area.

[0088] Experimental setup DSC tester model: TAInstrumentsDSC250.

[0089] Sample mass: 10 mg.

[0090] Heating range: room temperature to 200℃.

[0091] Heating rate: 10℃ / min.

[0092] Table name: Comparative data of curing time and heat release of Example 1 and Comparative Example 1.

[0093] This experiment verifies the significant effect of the curing accelerator cobalt acetate by comparing the curing reaction heat flow curves of Example 1 and Comparative Example 1. Experimental data show that the initial curing time of Example 1 with the addition of the curing accelerator is significantly shortened to about 5.5 minutes, which is more than 65% shorter than the average initial curing time (about 15 minutes) of Comparative Example 1 (without the curing accelerator). At the same time, the complete curing time of Example 1 is also shortened to 18-19 minutes, while the complete curing time of Comparative Example 1 is close to 45 minutes.

[0094] The curing accelerator cobalt acetate reduces the crosslinking activation energy between phenolic resin molecules through the catalytic action of metal ions, so that the reaction of methylol and phenolic hydroxyl groups proceeds more rapidly. This catalytic action accelerates the chain crosslinking process of the curing reaction, allowing the material to complete the formation of a high-density crosslinked network in a relatively short time. In Comparative Example 1, no accelerator is added, and the crosslinking reaction is completely dependent on the thermal activation process, resulting in a lower curing reaction rate and a longer duration of the exothermic process.

[0095] In addition, from the total exothermic peak area of ​​the heat flow curve, the peak area of ​​Example 1 increased by about 40% compared with Comparative Example 1, indicating that the introduction of cobalt acetate not only accelerated the curing reaction, but also improved the completeness of the reaction and formed a denser cross-linked network structure. A higher exothermic peak area means more cross-linking bonds are formed, which is directly related to the improvement of mechanical properties and thermal stability of the material during use.

[0096] In summary, this experiment fully demonstrates the significant effect of curing accelerator on improving curing efficiency and shortening curing time, and reveals its influence on cross-linking reaction rate and completeness through mechanism analysis. This result is consistent with the core innovation of the present invention, provides strong support for the industrial demand for rapid curing in practical applications, and lays an experimental foundation for subsequent performance optimization and practical application.

[0097] Experimental Example 2: Experimental procedures Sample preparation: Using the material formulas of Example 2 and Comparative Example 2, samples were prepared respectively: The toughening agent of Example 2 is liquid crystal polymer + polyurethane prepolymer (1:1).

[0098] The toughening agent of Comparative Example 2 is a single liquid crystal polymer.

[0099] The solidified granular material was prepared according to the process flow of Example 2 and Comparative Example 2.

[0100] Sample processing: The solidified material is processed into standard tensile and impact specimens in an injection molding machine: The tensile specimens conform to ASTM D638 standard (dumbbell shape).

[0101] The impact specimen complies with ASTM D256 standard (rectangular, with notch).

[0102] Tensile properties test: The tensile strength and elongation at break were tested using an electronic universal testing machine.

[0103] Test rate: 2mm / min.

[0104] Test environment: room temperature.

[0105] Impact performance test: The impact toughness was tested using an Izod impact tester.

[0106] Test temperature: room temperature.

[0107] Testing Log: Each group of samples was tested 5 times, and the data of tensile strength, elongation at break and impact toughness were recorded.

[0108] Experimental setup Device Model: Tensile properties testing equipment: Instron 5567 electronic universal testing machine.

[0109] Impact performance testing equipment: CEASTResil25 cantilever beam impact testing machine.

[0110] Test conditions: Room temperature (25±2℃).

[0111] Tensile specimen test rate: 2mm / min.

[0112] Energy of pendulum impacting the specimen: 2.75J.

[0113] Table name: Comparative data of tensile and impact properties of Example 2 and Comparative Example 2 This experiment verifies the significant synergistic effect of the multi-component toughening agent by comparing the tensile strength, elongation at break and impact toughness of Example 2 and Comparative Example 2. The experimental data show that the tensile strength of the material of Example 2 is 63.95MPa on average, while the tensile strength of the material of Comparative Example 2 is only 56MPa, and the strength is increased by about 14%. At the same time, the elongation at break of Example 2 is increased by more than 50%, and the impact toughness is increased by about 62%. These significant performance improvements are directly derived from the synergistic effect of the two-component toughening agent.

[0114] The combination of liquid crystal polymer and polyurethane prepolymer forms a multiphase dispersion system in the matrix material. Liquid crystal polymer has a rigid molecular chain structure and can form a high-strength microfiber phase in the matrix, effectively preventing the initiation and expansion of cracks. The polyurethane prepolymer provides toughness to the matrix through its flexible molecular chain, absorbs impact loads and disperses energy. The two toughening agents work synergistically to improve the strength of the material and improve its brittleness, making the material perform better in elongation at break and impact toughness.

[0115] In contrast, in Comparative Example 2, a single liquid crystal polymer was used for toughening. Although a rigid microfiber phase was formed, the material had poor toughness due to the lack of energy absorption capacity of the flexible phase, and the elongation at break and impact toughness were significantly lower than those in Example 2. This result further proves that a single toughening agent is difficult to take into account both the strength and toughness of the material at the same time, and the synergistic effect of the two-component toughening agent can effectively solve this problem.

[0116] The experimental results fully demonstrate the innovation and effectiveness of the design of the two-component toughening agent in the present invention in improving toughness performance. This toughening strategy not only improves the impact resistance of the material, but also ensures the adaptability of the material to high-load impact environments in industrial applications, providing a solid technical foundation for practical applications.

[0117] Experimental Example 3: Experimental procedures Sample preparation: Two groups of samples were prepared using the material formulations of Example 3 (boron nitride + graphene filler) and Comparative Example 3 (single boron nitride filler).

[0118] The materials were cured according to their respective formulations and preparation processes, and the cured materials were pressed into disc specimens with a diameter of 25 mm and a thickness of 2 mm.

[0119] Thermal conductivity test: The thermal conductivity of the samples was tested by laser flash method.

[0120] The sample is placed in the test cell of the laser flash instrument and a high-energy laser pulse is used to irradiate the sample surface while recording the thermal diffusivity, density and specific heat capacity of the sample.

[0121] Test conditions: Test temperature range: room temperature to 150°C, tested at intervals of 25°C.

[0122] Laser energy: 500mJ, pulse width: 10ns.

[0123] Data Records: Each group of samples was tested 3 times, and the average value was taken to record the thermal conductivity at each temperature.

[0124] Experimental setup Test equipment: Netzsch LFA467 laser flash meter.

[0125] Sample preparation conditions: The pressing pressure was 20 MPa and the holding time was 5 minutes. Temperature(℃) Sample No. Filling Thermal conductivity (W / m·K) 25 Example 3-1 Boron Nitride + Graphene 1.42 25 Example 3-2 Boron Nitride + Graphene 1.47 25 Comparative Example 3-1 Single Boron Nitride 1.12 25 Comparative Example 3-2 Single Boron Nitride 1.15 100 Example 3-1 Boron Nitride + Graphene 1.68 100 Example 3-2 Boron Nitride + Graphene 1.73 100 Comparative Example 3-1 Single Boron Nitride 1.34 100 Comparative Example 3-2 Single Boron Nitride 1.31 150 Example 3-1 Boron Nitride + Graphene 1.91 150 Example 3-2 Boron Nitride + Graphene 1.94 150 Comparative Example 3-1 Single Boron Nitride 1.45 150 Comparative Example 3-2 Single Boron Nitride 1.48

[0126] Table name: Thermal conductivity test data of Example 3 and Comparative Example 3 This experiment clarifies the synergistic effect of the composite thermal conductive filler by comparing the thermal conductivity of Example 3 and Comparative Example 3. The experimental results show that in the entire temperature range (25°C to 150°C), the thermal conductivity of the sample using the boron nitride + graphene composite filler in Example 3 is significantly higher than that of the sample using a single boron nitride in Comparative Example 3. At a high temperature of 150°C, the average thermal conductivity of Example 3 is 1.92W / m·K, while that of Comparative Example 3 is only 1.46W / m·K, an increase of nearly 32%.

[0127] The composite filler of boron nitride and graphene forms a more efficient heat conduction channel in the matrix material. Boron nitride is an excellent thermal conductor, and its lamellar structure helps to form a lateral heat conduction path in the matrix; graphene has a higher thermal conductivity coefficient, and through the synergistic effect with boron nitride, it can effectively fill the microscopic gaps and further reduce the thermal resistance of the material. In contrast, although the single boron nitride filler in Comparative Example 3 can improve the thermal conductivity of the material, it lacks the auxiliary effect of graphene and cannot form an efficient heat conduction network, so the thermal conductivity coefficient is low.

[0128] In addition, from the perspective of temperature change, the thermal conductivity of Example 3 increases more significantly with increasing temperature, indicating that the thermal conduction channel of the composite system of boron nitride and graphene is more stable in a high temperature environment. This synergistic effect is not only reflected in the improvement of thermal conductivity, but also improves the thermal stability and high temperature application performance of the material to a certain extent.

[0129] Experimental results show that the design of composite fillers greatly improves the thermal conductivity of the material, especially under high temperature conditions.

[0130] Experimental Example 4: Experimental procedures Sample preparation: The samples were prepared using the formulations of Example 1 (containing a multifunctional additive), Example 2 (containing a multifunctional additive and a two-component toughening agent) and Comparative Example 4 (without a multifunctional additive).

[0131] After curing, each group of samples was pressed into a standard tensile specimen (in accordance with ASTM D638 standard).

[0132] Thermal aging test: The samples were placed in a heat aging box, set at 150°C, kept at a constant temperature for 72 hours, and samples were taken every 24 hours.

[0133] Test the change rate of tensile strength before and after aging, and record the tensile strength retention rate.

[0134] UV aging test: Use a UV aging box (wavelength 340nm), set the temperature to 50°C and the humidity to 60%, and irradiate continuously for 200 hours.

[0135] Samples were taken every 50 hours to observe the color changes on the sample surface and test the tensile strength retention rate.

[0136] Salt spray corrosion test: The sample was placed in a salt spray box, 5% NaCl solution was used, the temperature was set at 50°C, and sprayed for 72 hours.

[0137] Test the change rate of tensile strength before and after corrosion, and record the tensile strength retention rate.

[0138] Data Records: Each group of samples was tested three times under each aging condition and the average value was calculated.

[0139] Experimental setup Device Model: Thermal aging box: Memmert UN110.

[0140] UV aging box: Q-LABQUV / se.

[0141] Salt spray chamber: C&WSF / 450.

[0142] Test conditions: Heat aging: 150℃, constant temperature for 72 hours.

[0143] UV aging: wavelength 340nm, 50℃, humidity 60%, 200 hours.

[0144] Salt spray corrosion: 5% NaCl solution, 50°C, spray for 72 hours.

[0145] Mechanical properties test: The tensile properties were measured according to ASTM D638 using an Instron 5567 electronic universal testing machine. Sample No. Type of aging Aging time (one hour) Tensile strength retention rate (%) Example 1-1 Heat aging 24 95.2 Example 1-2 Heat aging 72 88.7 Comparative Example 4-1 Heat aging 24 83.4 Comparative Example 4-2 Heat aging 72 68.9 Example 2-1 UV aging 50 93.1 Example 2-2 UV aging 200 84.5 Comparative Example 4-3 UV aging 50 78.6 Comparative Example 4-4 UV aging 200 65.2 Examples 1-3 Salt spray corrosion 72 90.3 Examples 1-4 Salt spray corrosion 72 88.9 Comparative Examples 4-5 Salt spray corrosion 72 72.8

[0146] Table name: Comparative data of anti-aging performance of Example 1, Example 2 and Comparative Example 4 This experiment compared the performance changes of Example 1, Example 2 and Comparative Example 4 under three conditions of thermal aging, ultraviolet aging and salt spray corrosion, and verified the significant contribution of multifunctional additives to the anti-aging performance of materials. The experimental data showed that the tensile strength retention rate of Example 1 and Example 2 was significantly higher than that of Comparative Example 4, especially under high temperature and ultraviolet aging conditions, the multifunctional additive significantly delayed the attenuation of material performance.

[0147] The introduction of antioxidants effectively prevents the degradation reaction of the material due to oxidation under high temperature conditions, thereby ensuring the integrity of the molecular chain and significantly improving the thermal aging performance. The tensile strength retention rate of Example 1 after 72 hours in the thermal aging test is 88.7%, while that of Comparative Example 4 is only 68.9%, proving that the antioxidant has a significant effect.

[0148] The UV aging test further showed that the UV stabilizer reduces the destructive effect of UV on the molecular chain of the material by absorbing UV radiation and converting it into low-energy heat. In Example 2, due to the synergistic effect of the multifunctional additive and the two-component toughening agent, not only does it show better UV resistance, but the tough matrix also effectively alleviates the stress concentration phenomenon of crack propagation, and the tensile strength retention rate is significantly improved.

[0149] The salt spray corrosion test shows that the rust inhibitor introduced in Examples 1 and 2 forms a stable protective film on the surface of the material, significantly reducing the erosion of the material by the NaCl solution. Due to the lack of protection of the multifunctional additive, the surface of Comparative Example 4 was significantly corroded and deteriorated, resulting in a tensile strength retention rate of only 72.8%, while the retention rate of Example 1 was as high as 90.3%.

[0150] In summary, the experimental results prove that the multifunctional additive has significant effects in anti-oxidation, anti-ultraviolet and anti-corrosion. The comprehensive performance of Example 1 and Example 2 is significantly better than that of Comparative Example 4, providing strong technical support for the long-term application of the material in harsh environments. This result also fully reflects the innovation of the present invention in the design of anti-aging performance.

[0151] Experimental Example 5: Experimental procedures Preparation of coated sand: The high-performance phenolic resin materials of Example 1, Example 3 and Comparative Example 4 were used as coating materials.

[0152] Preparation method of coated sand: The phenolic resin material was mixed with quartz sand at a weight percentage of 5%.

[0153] The mixture was stirred evenly in a mixer, the stirring rate was controlled to be 100 rpm, and the stirring time was 15 minutes.

[0154] Heat to 180°C to evenly coat the resin on the surface of the quartz sand, and then dry to obtain coated sand.

[0155] Compressive strength test: The prepared coated sand is loaded into the compressive strength test mold and loaded step by step using a compression testing machine until the sand body breaks.

[0156] Test temperature: 150℃ and 200℃.

[0157] Loading rate: 10MPa / min.

[0158] Flow diversion performance test: The coated sand was loaded into a conductivity test device, and the conductivity of the sand body was measured under simulated oil well fracturing conditions (pressure 50 MPa, temperature 150°C).

[0159] The conductivity is calculated by the volume of fluid passing through the sand body per unit time.

[0160] Repeat the test: Each group of samples was tested three times, and the compressive strength and flow conductivity data were recorded.

[0161] Experimental setup Device Model: Compression strength testing machine: Instron5969.

[0162] Flow diversion test device: a self-made high-pressure and high-temperature fluid measurement system.

[0163] Test conditions: Compression test temperature: 150℃, 200℃.

[0164] Diversion test pressure: 50MPa.

[0165] Test medium: simulated oil field fracturing fluid. Test temperature (℃) Sample No. Resin source Compressive strength(MPa) <![CDATA[Flow conductivity (m 3 / h)]]> 150 Example 1-1 Example 1 15.8 1.02 150 Example 1-2 Example 1 16.3 1.05 150 Comparative Example 4-1 Comparative Example 4 12.5 0.87 150 Comparative Example 4-2 Comparative Example 4 12.3 0.83 200 Example 3-1 Example 3 14.6 0.97 200 Example 3-2 Example 3 14.8 1.01 200 Comparative Example 4-3 Comparative Example 4 10.9 0.72 200 Comparative Example 4-4 Comparative Example 4 10.7 0.69

[0166] Table name: Compressive strength and flow conductivity data of coated sand of Example 1, Example 3 and Comparative Example 4. This experiment verified the high efficiency of the phenolic resin material of the present invention in the application of coated sand by comparing the compressive strength and flow conductivity of Example 1, Example 3 and Comparative Example 4. Experimental data show that the coated sand of Example 1 and Example 3 exhibited significantly better compressive strength and flow conductivity than Comparative Example 4 at high temperatures of 150°C and 200°C. Taking 200°C as an example, the average compressive strength of Example 3 is 14.7MPa, while that of Comparative Example 4 is only 10.8MPa, an increase of nearly 36%. The flow conductivity is also significantly improved, with the flow conductivity of Example 3 being 1.01m 3 / h, while the comparative example 4 is only 0.71m 3 / h.

[0167] The modified phenolic resin materials used in Examples 1 and 3 maintain a high crosslinking density and mechanical strength under high temperature conditions, which is derived from the stability of the high crosslinking density molecular network, while the ordinary phenolic resin of Comparative Example 4 is insufficiently crosslinked, resulting in the collapse of the sand body structure under high temperature and high pressure conditions, and the compressive performance is significantly reduced. In Example 3, the thermal conductivity of the material is further improved through the synergistic effect of the thermal conductive filler (boron nitride + graphene), which effectively reduces the internal heat accumulation of the sand body and improves the compressive and flow conductivity.

[0168] In addition, the multifunctional additives (such as antioxidants and rust inhibitors) in Examples 1 and 3 further enhanced the anti-aging properties of the materials, and maintained good conductivity under the erosion conditions of simulated fracturing fluid. However, in Comparative Example 4, the lack of additive protection aggravated the chemical degradation of the material in a high temperature and saline environment, resulting in a rapid decrease in conductivity and compressive resistance. This result verifies the importance of multifunctional additives to the long-term performance of coated sand.

[0169] The experimental results show that the present invention effectively solves the problem of insufficient strength and decreased conductivity of traditional coated sand under high temperature and high pressure conditions by optimizing the modified design of phenolic resin and the composite matching of multi-component fillers. The thermal conductivity and compressive resistance of Example 3 are outstanding, and it is particularly suitable for ultra-deep wells or high-temperature fracturing environments, while Example 1 is a highly versatile material suitable for conventional fracturing operations. This result fully reflects the technical advantages and practical value of the material of the present invention in the field of petroleum fracturing.

[0170] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A high performance phenolic resin material, characterized in that: The material comprises the following components by weight percentage: 60% to 75% of modified phenolic resin, 5% to 15% of curing accelerator, 10% to 20% of toughening agent, 5% to 20% of filler, and 3% to 10% of multifunctional additive.

2. A high performance phenolic resin material according to claim 1, characterized in that: The modified phenolic resin is prepared by the following steps: The phenolic compound and the formaldehyde solution are mixed in a reaction kettle, and an alkaline catalyst is added to react to obtain a phenolic prepolymer; gradually adding a modifier containing a hydroxyl group, an epoxy group, and a carboxyl group to the phenolic prepolymer while stirring to obtain a mixture; The obtained mixture is heated to react to complete the cross-linking modification reaction to obtain a modified phenolic resin; The modified phenolic resin is cooled to room temperature and then used for later use.

3. A high performance phenolic resin material according to claim 1, characterized in that: The curing accelerator is one or more metal salt compounds, and the metal salt compounds include cobalt acetate and zinc acetate.

4. A high performance phenolic resin material according to claim 1, characterized in that: The toughening agent is one or more of low molecular weight polyether, liquid crystal polymer or polyurethane prepolymer.

5. A high performance phenolic resin material according to claim 1, characterized in that: The filler includes one or more of the following: Boron nitride, graphene, carbon nanotubes, zirconium oxide ceramic powder, surface modified glass microspheres.

6. A high performance phenolic resin material according to claim 1, characterized in that: The multifunctional additives include one or more of the following: ultraviolet stabilizers, antioxidants, and rust inhibitors.

7. A method for preparing a high-performance phenolic resin material, based on a high-performance phenolic resin material according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1. In a reaction kettle, dissolving the modified phenolic resin in an organic solvent to form a uniform solution; S2, gradually adding a curing accelerator, a toughening agent and a filler to the solution, stirring and mixing until uniformly dispersed; S3, preliminarily curing the mixed solution to form a cured prepolymer; S4, further heating the cured prepolymer for secondary curing to obtain a high-performance phenolic resin material; S5. Cool the solidified product to room temperature and crush it into granules.

8. The method for preparing a high-performance phenolic resin material according to claim 7, characterized in that: The dissolution process of the modified phenolic resin in step S1 is carried out at a temperature of 60 to 80° C., and the filler in step S2 is uniformly dispersed by ultrasonic vibration or high shear stirring equipment, with a stirring rate of 5000 to 6000 rpm and a dispersion time of 10 to 30 minutes.

9. The method for preparing a high-performance phenolic resin material according to claim 7, characterized in that: The preliminary curing in step S3 is carried out by controlling the temperature at 100-120° C. for 1-2 hours, and the curing degree reaches 70%-80%; The secondary curing in step S4 is carried out at a temperature of 150 to 180° C. for 1 to 2 hours, and further cross-linked to complete curing; The solidified product after cooling in step S5 is crushed by a mechanical crusher to prepare a granular high-performance phenolic resin material with a particle size of 10 to 50 microns.

10. A coated sand, characterized in that: The coating material of the coated sand is the high-performance phenolic resin material as described in claims 1-6.

Citation Information

Cited By

  • V-method precise resin sand mold casting process method suitable for gray iron or ductile iron

    CN120286635A

  • High-performance modified phenolic resin plastic and preparation method thereof

    CN120888159A